Combined Scalable Video Coding Method for Wireless Transmission - Kalvein Rantelobo; Wirawan Wirawan; Gamantyo Hendrantoro; Achmad Affandi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Mobile video streaming is one of multimedia services that has developed very rapidly. Recently, bandwidth utilization for wireless transmission is the main problem in the field of multimedia communications. In this research, we offer a combination of scalable methods as the most attractive solution to this problem. Scalable method for wireless communication should adapt to input video sequence. Standard ITU (International Telecommunication Union) - Joint Scalable Video Model (JSVM) is employed to produce combined scalable video coding (CSVC) method that match the required quality of video streaming services for wireless transmission. The investigation in this paper shows that combined scalable technique outperforms the non-scalable one, in using bit rate capacity at certain layer.